Investigation on thermal dechlorination and catalytic pyrolysis in a continuous process for liquid fuel recovery from mixed plastic wastes - Lei, Junxi (2017)
A continuous system (feeding rate >1 kg/h) consisting of thermal dechlorination pre-treatment and catalytic pyrolysis with Fe-restructured clay (Fe-RC) catalyst was developed for feedstock recycling of PVC-containing mixed plastic waste. The vented screw conveyor which was specially designed for continuous dechlorination was able to achieve dechlorination efficiency of over 90 % with a feedstock retention time longer than 35.5 min. The chlorine content of the pyrolytic oil obtained after dechlorination was in the range of 6.08–39.50 ppm, which meet the specification for reclamation pyrolytic oil in Japan. Fe-RC was found to significantly improve the yield of pyrolytic oil (achieved to 83.73 wt%) at the optimized pyrolysis temperature of 450 °C and catalyst dosage of 60 g. With the optimized parameters, Fe-RC showed high selectivity for the C9–C12 and C13–C19 oil fraction, which are the major constituents of kerosene and diesel fuel, demonstrating that this catalyst can be applied in the pyrolysis of mixed plastic wastes for the production of kerosene and diesel fuel. Overall, the continuous process exhibited high stability and consistently high-oil yield upon reaching steady state, indicating its potential up-scaling application in the industry.